How Research Evidence is Defined, Acquired, and Shared Across Systems That Address Intimate Partner Violence - Lindhorst, Taryn P. (Violence against women, 2022)
This exploratory study examined the flow of research evidence through systems that address intimate partner violence (IPV), including victim services, law enforcement, and criminal justice organizations. Qualitative interviews with representatives of these disciplines assessed how respondents define, acquire, and share research evidence. Findings suggest that research evidence is defined more broadly in the field than in academic settings, and is accessed primarily from trusted intermediaries within professional networks. State IPV coalitions and victim service providers are key intermediaries across sectors. Findings suggest the need for more tangible supports to support sharing of research information within and across service sectors.